LUCY’S FAILURE TO FREE HERSELF FROM MALE DOMINATION IN JAMAICA KINCAID’S LUCY - Aris Siswanti (ISSN)
Considering Lucy’s failure in her struggle, this study was conducted to see (1) why Lucy struggles, (2) how she struggles, and (3) why she fails in her struggle. This study was designed by a qualitative research, which intended to describe the data taken from the novel. These data were analyzed using content analysis in the framework of feminist theory of the first-wave and second–wave feminism and feminist theory by Robbins. The result of the study shows that considering Annie’s treatment on her daughter, she is representing the male domination on Lucy. Therefore, Lucy struggles by making her own life which is free from male domination Annie stands with. Her failure happens because she has internalized her mother’s values that she even comes deeper into her mother and men’s domination and emphasizes the male authority on her.